Testing Fertilizer Application on Melon Plant Growth and Yield (Cucumis melo L.) - Ida Ayu Widhiantari; Bahrul Sundusi Adnan; Nani Herwati; Slamet Nugroho (Jurnal Online Pertanian Tropik, 2026)
This study aims to investigate the effect of KNO₃ fertilizer application on the growth of melon plants during the vegetative and early generative phases. Melon was selected due to its high economic value; however, its productivity has declined as a result of suboptimal cultivation techniques, particularly in fertilizer management. The research was conducted at the Center for Agricultural Application and Modernization (BRMP) in West Nusa Tenggara using a one-factor Completely Randomized Design (CRD) with five KNO₃ dosage treatments (1, 3, 5, 7, and 9 g/L), each replicated three times. Observed parameters included plant height, number of leaves, number of male and female flowers, number of fruit initials, and fruit diameter. Data were analyzed using ANOVA followed by the DMRT post-hoc test at a 5% significance level. The results indicated that although the 5 g/L treatment tended to yield better results, particularly in the number of flowers and fruit diameter, statistically, all treatments showed no significant effect. Constraints such as pest attacks, pollination disturbances, and plant diseases were identified as non-nutritional factors affecting crop outcomes.